Young Athletes In Training Game Forms And Methods (Texas Journal of Multidisciplinary Studies, 2025)
This article discusses the issues and problems of maximizing the body's capabilities due to the special emotional background created by the game situation or the competition process, which enhances the effect of physical exercises and reserves that are not detected in the usual conditions of training sessions